Under one roof? Left‐behind children's perspectives in negotiating relationships with absent and return‐migrant parents. Issue 3 (15th April 2018) - Lam, Theodora; Yeoh, Brenda S.A.
Abstract: Children—whether left behind or as migrants—have remained largely invisible in Southeast Asian migration scholarship. Their experiences and perspectives on migration, as well as how they demonstrate agency within the limits of culturally/socially constructed childhoods influenced by a "hybridisation" of global and local conditions, are often overlooked in favour of adults'. This article addresses this research lacuna by focusing attention on how left‐behind Indonesian and Filipino children between 9 and 11 years of age engage and react to the changes in their everyday lives brought about by both parental migration and parental return. Using both quantitative and qualitative data collected from a larger study on child health and migrant parents in Southeast Asia with return‐migrants, left‐behind carers, and children, this article highlights the experiences of left‐behind children by revealing their agency and creativity in managing changes in their daily lives due to the frequent and transient comings and goings of one or both parents.